2023
DOI: 10.3390/jfb14050280
|View full text |Cite
|
Sign up to set email alerts
|

Development of Salmon Sperm DNA/Regenerated Silk Bio-Based Films for Biomedical Studies on Human Keratinocyte HaCaT Cells under Solar Spectrum

Abstract: In this study, we fabricated adhesive patches from silkworm-regenerated silk and DNA to safeguard human skin from the sun’s rays. The patches are realized by exploiting the dissolution of silk fibers (e.g., silk fibroin (SF)) and salmon sperm DNA in formic acid and CaCl2 solutions. Infrared spectroscopy is used to investigate the conformational transition of SF when combined with DNA; the results indicated that the addition of DNA provides an increase in the SF crystallinity. UV–Visible absorption and circular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…This indeed suggests that the main structure of the employed DNA solutions is the B-form. We observed that the DNA retains this structure also when inserted in the SF matrix, as reported in a previous work . Moreover, UV–vis spectra of the initial SF/DNA solutions and films were measured and compared, as shown in Figure c.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…This indeed suggests that the main structure of the employed DNA solutions is the B-form. We observed that the DNA retains this structure also when inserted in the SF matrix, as reported in a previous work . Moreover, UV–vis spectra of the initial SF/DNA solutions and films were measured and compared, as shown in Figure c.…”
Section: Resultssupporting
confidence: 81%
“…We observed that the DNA retains this structure also when inserted in the SF matrix, as reported in a previous work. 35 Moreover, UV−vis spectra of the initial SF/DNA solutions and films were measured and compared, as shown in Figure 1c. The absorption spectrum of SF film appears to be very similar to that of the native solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations